AROMA TERAPI LAVENDER TERHADAP KECEMASAN PASIEN PRA OPERASI KATARAK - Elisa Anderson; Juwyensi A. Taareluan (NUTRIX, 2019)
Surgery is a medical procedure that can trigger anxiety, lavender aromatherapy is one alternative intervention that can be done to overcome this anxiety. The purpose of this study was to analyze the effect of lavender aroma therapy on the anxiety of pre cataract surgery patients. The research method used was quasi experimental pre and post test with control group design. This study was conducted on 30 respondents selected through consecutive sampling technique and divided into two groups, namely 15 people in the control group and 15 people in the treatment group. The results of this study showed that through the Wilcoxon test found p=0.008, there was a significant effect of lavender aromatherapy on anxiety in the treatment group. In the Mann Whitney test found p=0.006, there was a significant difference in the effect of lavender aromatherapy on anxiety in the treatment and control groups. Thus, there is a significant effect of the lavender aromatherapy on the anxiety of pre-cataract surgery patients. Nurses can provide aromas of lavender therapy to reduce the anxiety of preoperative patients so that the surgical procedure can work well.